Tax evasion and the marginal cost of public funds - Usher, D. (Kingston, Ontario Department of Economics, Queen's University, 1986)
Tax evasion is analogous to dead weight loss in its effect upon the rules for cost-benefits analysis of public sector projects. Dead weight loss and tax evasion both cause the marginal cost of public funds to increase in tax rates. In one case, the social cost id from the diversion of resources from highly taxed to less taxed activities. In the other, the social cost includes the expense of concealment of income from the tax collector, the cost of the public sector detecting and punishing tax evasion, and the cost of punishment to the convicted tax evader. It follows from this line or reasoning that a complete theory of optimal taxation can be derived from the susceptibilities to evasion of the different means of taxation.
"January 1986."
Discussion paper.
Includes bibliographical references (pages 44-45).
Keywords: Tax evasion -- Mathematical models